2007
DOI: 10.1021/jp068203i
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anions on Intervalence Charge Transfer (IVCT) in Mixed-Valence Dinuclear Complexes

Abstract: Spectroelectrochemical studies of the intervalence charge transfer (IVCT) characteristics of both diastereoisomeric forms of the dinuclear complex [{Ru(bpy)2}2(mu-dpi-)]n+ [bpy=2,2'-bipyridine; dpi-=4,5-di(2-pyridyl)imidazolate] showed that the degree of inter-metal electronic coupling (or valence delocalization) is dependent on stereochemical identity. Increasing the relative concentration of the strongly associating anion toluene-4-sulfonate in acetonitrile/[(n-C4H9)4N]{B(C6F5)4} solution differentially decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Irrespective of the identity of the oxidation sites, the use of a croconate instead of a dicarboxylate bis(chelate) increases the thermodynamic stabilities of the mixed-valent forms as evident from the enhanced Δ E 1/2 values between the 0/+ and +/2+, or the 2+/3+ and the 3+/4+ redox couples. While the sizable effects of the anion of the supporting electrolyte point towards a significant contribution of electrostatic effects to the observed redox splittings, electrochemical studies per se are inconclusive as to whether this increase in redox splitting also entails contributions from improved electron delocalization [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. The presence or absence of electronic coupling can, however, be probed by combining (electro)chemical oxidation with IR and UV/Vis/NIR spectroscopy, and this is the subject of the following section.…”
Section: Resultsmentioning
confidence: 99%
“…Irrespective of the identity of the oxidation sites, the use of a croconate instead of a dicarboxylate bis(chelate) increases the thermodynamic stabilities of the mixed-valent forms as evident from the enhanced Δ E 1/2 values between the 0/+ and +/2+, or the 2+/3+ and the 3+/4+ redox couples. While the sizable effects of the anion of the supporting electrolyte point towards a significant contribution of electrostatic effects to the observed redox splittings, electrochemical studies per se are inconclusive as to whether this increase in redox splitting also entails contributions from improved electron delocalization [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. The presence or absence of electronic coupling can, however, be probed by combining (electro)chemical oxidation with IR and UV/Vis/NIR spectroscopy, and this is the subject of the following section.…”
Section: Resultsmentioning
confidence: 99%
“…The access to the diastereosiomeric forms gives a particular opportunity for an intimate insight into anion participation in the charge-transfer process. 52,58, 59 A study of the spectroelectrochemical study of the IVCT characteristics of rac-and meso-[{Ru(bpy) 2 } 2 (m-dpi -)] n+ {dpi -= 4,5-di(2-pyridyl)imidazolato (Fig. 2m)} 59 showed that the degree of inter-metal electronic coupling was dependent on stereochemical identity.…”
Section: Effect Of Anionsmentioning
confidence: 99%
“…52,58, 59 A study of the spectroelectrochemical study of the IVCT characteristics of rac-and meso-[{Ru(bpy) 2 } 2 (m-dpi -)] n+ {dpi -= 4,5-di(2-pyridyl)imidazolato (Fig. 2m)} 59 showed that the degree of inter-metal electronic coupling was dependent on stereochemical identity. Increasing the relative concentration of the strongly-associating anion toluene-4-sulfonate in acetonitrile/[N(n-C 4 H 9 ) 4 ]{B(C 6 H 5 ) 4 } solution differentially decreased the level of electron delocalisation for the two diastereoisomers, although the extent of anion-induced localisation was modest.…”
Section: Effect Of Anionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dye sensitizer is regarded as the key component which governs the photovoltaic performance of DSSCs [2]. Different strategies are adopted to optimize the performance of ruthenium bipyridyl-based complexes to fit specific functionalities, namely, employing different ancillary ligands [2], using light harvesting antennas which funnel their photonic excitation to the dye sensitizer modules [14,15], or designing spacers (bridging ligands) which separate photoactive terminals [16][17][18], among others. The role of bridging ligands is particularly attractive for they not only allow control over the spatial arrangement of the complexes but also provide an insight into the electronic coupling of the separated metal centers [19].…”
Section: Introductionmentioning
confidence: 99%